The Strategy of the Work of Religious Associations with Immigrants: from Social Adaptation to the Mission - Roman Lunkin (Научно-аналитический вестник Института Европы РАН, 2019)
In the article analyzed the role of the religious associations in their work with migrants from different countries on the example of the activities of the set of Christian churches in Russia and European Union. That kind of mission plays a special role in the conditions when the waves of inner migration and immigrant crisis touch all Eurasian space. The Strategy of the Christian missions based on the social work, not on the direct mission for converting of the migrants in the certain communities. The main part of the migrants (in Russia, for example, from Northern Caucasus) and immigrants (from Central Asia and Middle East) belong to the muslim culture and they were come from the traditional society with its own clan rules. In connection with that the mission proceeds from the social and legal help and social adaption in the first hand for those who need it. The cultural and religious missions became the next period of the integration of the migrants into society.